Cross-Sectional Associations between HDL Structure or Function, Cell Membrane Fatty Acid Composition, and Inflammation in Elderly Adults. Issue 3 (23rd November 2021) - Muralidharan, Jananee; Papandreou, Christopher; Soria-Florido, Maria T; Sala-Vila, Aleix; Blanchart, Gemma; Estruch, Ramon; Martínez-González, Miguel A; Corella, Dolores; Ros, Emilio; Ruiz-Canela, Miguel; Fito, Montse; Salas-Salvadó, Jordi; et al.
ABSTRACT: Background: Cell membrane fatty acid composition has been related to inflammation and cardiovascular disease (CVD) risk. Dysregulation of HDL function is also considered a CVD risk factor. Objectives: We aimed to investigate whether the content of cell membrane fatty acids and HDL functionality are linked to each other as well as to inflammation. Methods: This cross-sectional analysis involved 259 participants (mean age: 67.9 y) with overweight/obesity (mean BMI: 29.5 kg/m 2 ) from a coronary artery disease case-control study nested within the PREDIMED (PREvención con DIeta MEDiterránea) trial for which HDL functional parameters [apoA-I, apoA-IV, and apoC-III; cholesterol efflux capacity (CEC); HDL oxidative inflammatory index (HOII); sphingosine-1-phosphate (S1P); serum amyloid A (SAA); and complement-3 (C3) protein] were quantified. We also assessed 22 fatty acids in blood cell membranes using GC and inflammatory markers (IFN-γ and IL-1b, IL-6, IL-8, and IL-10) in serum. Associations of HDL-related variables with cell membrane fatty acids and with inflammatory markers were assessed using multivariable linear regression analyses with elastic net penalty. Results: ApoA-I, apoC-III, CEC, HOII, S1P, and SAA, but not apoA-IV and C3 protein, were associated with membrane fatty acids. S1P and SAA were directly associated with IL-6, whereas apoA-I and C3 protein showed inverse associations with IL-6. Specific fatty acids including myristic acid (14:0) and long-chain n–6 fatty acids being negatively and positively associated with IL-8, respectively, were also found to be positively associated with SAA. Conclusions: This study suggests interrelations between indicators of inflammation and both blood cell membrane fatty acid composition and HDL structure/functional parameters in a Mediterranean population at high CVD risk. This trial was registered at www.isrctn.com as ISRCTN35739639.